2019
DOI: 10.1186/s13195-019-0505-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety correlates with cortical surface area in subjective cognitive decline: APOE ε4 carriers versus APOE ε4 non-carriers

Abstract: Background Subjective cognitive decline (SCD) is characterized by self-reported cognitive deficits without measurable cognitive impairment. It has been suggested that individuals with SCD exhibited brain structural alterations in widespread cortical thinning or gray matter loss in the medial temporal and frontotemporal regions. Apolipoprotein E ( APOE ) ε4 allele is thought to be a genetic marker associated with risk of SCD. Neuropsychiatric symptoms may provide insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 61 publications
1
17
1
Order By: Relevance
“…The heterogeneity of SCD may be one of the causes of the inconsistent results, as evidence has suggested that patients with clinically defined SCD who present with smaller brain volumes have a higher risk of developing dementia than community-recruited subjects with SCD [ 23 ]. When combined with genetic risk factors, SCD subjects who are ApoE ɛ4 carriers showed more severe atrophy in the left hippocampus [ 84 ] and an additive reduction in the right cortical surface area [ 85 ] than noncarriers; this outcome is consistent with the results from longitudinal studies [ 86 ]. Furthermore, some studies have investigated the volumetric differences in subcortical regions, including the cholinergic basal forebrain nuclei and the hippocampal subfield, between individuals with SCD and HCs.…”
Section: Structural Mri and Diffusion Mrisupporting
confidence: 59%
See 1 more Smart Citation
“…The heterogeneity of SCD may be one of the causes of the inconsistent results, as evidence has suggested that patients with clinically defined SCD who present with smaller brain volumes have a higher risk of developing dementia than community-recruited subjects with SCD [ 23 ]. When combined with genetic risk factors, SCD subjects who are ApoE ɛ4 carriers showed more severe atrophy in the left hippocampus [ 84 ] and an additive reduction in the right cortical surface area [ 85 ] than noncarriers; this outcome is consistent with the results from longitudinal studies [ 86 ]. Furthermore, some studies have investigated the volumetric differences in subcortical regions, including the cholinergic basal forebrain nuclei and the hippocampal subfield, between individuals with SCD and HCs.…”
Section: Structural Mri and Diffusion Mrisupporting
confidence: 59%
“… Sanchez-Benavid et al, (2018) [ 72 ] 1 binary question and SCD-Q questionnaire T1 MRI Cross-sectional NC: n = 2098 (55.41 ± 6.62) SCD-: n = 319 (55.62 ± 6.22) SCD+: n = 253 (59.10 ± 7.12) SCD+ subjects showed lower gray matter volumes. Sun et al, (2019) [ 85 ] Memory clinic consultation for < 5 y SCD T1 MRI Cross-sectional NC: n = 73 (64.55 ± 5.52) SCD: n = 65 (65.85 ± 4.85) Decreased total cortical volumes and cortical surface area in SCD. SCD ApoE ɛ4 carriers showed additive reduction in the right cortical surface area.…”
Section: Structural Mri and Diffusion Mrimentioning
confidence: 99%
“…Surrounding areas including the parahippocampal gyrus are considered sites of very early formation of neuro brillary tangles in AD including early volume loss. our results have some differences from previous reports [13,44]: we did not nd signi cant cortical thickness differences between controls and SCD, which may be related to a small sample size. In addition, other factors might have also contributed to discrepant ndings between our study, e.g., the way of recruitment may in uence the results within a speci c sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to MCI in Alzheimer's disease (AD), PD-MCI frequently includes an increased severity of executive and visuospatial deficits and a decreased severity of memory impairment (Aarsland, 2016;Jellinger and Korczyn, 2018). Moreover, considering that ApoE is a well-recognized susceptibility gene for AD (Sun Y. et al, 2019), it is still far from clear whether the effects of this gene are different in PD patients.…”
Section: Introductionmentioning
confidence: 99%